2020
DOI: 10.1016/j.ijid.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use among hospitalized adult patients in a setting with limited laboratory infrastructure in Freetown Sierra Leone, 2017–2018

Abstract: A total of 920 patients were interviewed, of which 753 (81.8%) had at least one antibiotic. Complete data was captured for 688 (91.0%) patients. The median age was 41 years and 52.8% were male. Fever was reported in 41.5% of patients, though 85.1% had no leukocyte count prior to antibiotic use and none had a bacterial culture. Indications for prescribing were surgical prophylaxis (15.7%), pneumonia (15.1%), and trauma (5.8%). Cephalosporins (25.9%), penicillins (23.2%), and imidazoles (20.8%) were commonly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 18 publications
5
33
1
Order By: Relevance
“…Although there were existing antibiotic guidelines in this hospital, their use could not provide adequate guidance to the treatment of HAP and CAUTI. Nonetheless, antibiotics used by patients in this study were mainly first or second line similar to findings in a recent study on antibiotic use in this hospital [26].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although there were existing antibiotic guidelines in this hospital, their use could not provide adequate guidance to the treatment of HAP and CAUTI. Nonetheless, antibiotics used by patients in this study were mainly first or second line similar to findings in a recent study on antibiotic use in this hospital [26].…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, carbapenem-resistance rate in A. baumannii, P. aeruginosa, and Enterobacteriaceae were lower than reported in other LMICs [29,30] and some high-income countries [31]. These patterns of antibiotic resistance in this setting could be explained by the high rate of use of third generation cephalosporins and a lack in exposure of admitted patients in this hospital to carbapenems [26]. Moreover, the carbapenem resistance rate to E. cloacae may reflect elevated minimum inhibitory concentrations (MICs) they sometimes display or may also reflect an error on the susceptibility instrument.…”
Section: Discussionmentioning
confidence: 55%
“…In a study involving the analysis of prescriptions form the outpatients' department (OPD), Cole et al concluded that medicines were not rationally prescribed for children underfive as per WHO prescribing indicators 11 . Similar findings from a study focusing on antibiotic prescribing at a national level 12 and antibiotics use for none bacterial infection, and prophylaxis 13 have also been reported, which might explain the high prevalence of multidrug resistance bacteria in Sierra Leone 14,15 . The key reason for this trend, according to the WHO and empirical evidence, is the shortage of skilled health workers, fragility in the health system; 16,17 limited diagnostics capacity in most hospitals and inadequate regulatory framework on the import and sales of pharmaceuticals 13,17 .…”
Section: Introductionsupporting
confidence: 76%
“…Strengthening our core laboratory generated value by establishing stronger partnerships across disciplines and repurposing otherwise latent infrastructure and human resource capacity. The collective experiences from past transnational collaborations by the authors [3][4][5][6][7][8], culminated in the vision to establish the COVID19 laboratory and its unprecedented execution in two weeks. The laboratory is now an accredited COVID19 testing site under the Nigeria Center for Disease Control (NCDC) Network.…”
Section: A New Institutional Capacity Standard For Developing Countriesmentioning
confidence: 99%